Application of Multiple Regression in Estimating the Amount of Population Growth in Siantar District - Ayu Wulandari; Agus Perdana Windarto; Hendry Qurniawan (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study is to solve a case or problem that makes decision makers experience various obstacles in estimating the amount of population growth each year by using multiple linear regression algorithms as a solution to solving cases. The data used in this study was obtained directly from the official website of the Central Statistics Agency (BPS) Simalungun in the form of a softcopy book file entitled